Experience with the Start of Operation of ŠKODA Single-Deck EMUs (Current Problems in Rail Vehicles, 2025)
The paper concerns the homologation and commissioning procedure for EMUs of types 16Ev and 21Ev operated on railways in Latvia and Estonia. The first part covers the testing and type approval of the EMUs, while the second part describes the experience of operation and servicing of the EMUs in connection with weather conditions in the Baltics. The last part of the paper is focused on the experience of EU operation in general and the most common effects on vehicle availability in the Czech Republic.
Keywords: electric multiple unit; homologation; commissioning; failures; maintenance; operation under warranty; full service